2016
DOI: 10.1136/gutjnl-2016-311819
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of two faecal immunochemical tests in population-based colorectal cancer screening

Abstract: NTR5385; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…By contrast, two population-based studies conducted in Latvia and in the Netherlands observed significant differences in PRs between two different FIT brands (OC Sensor and FOB Gold), in spite of applying an identical threshold (10 mg Hb/g feces). 48,49 Furthermore, even large differences in the PR (12.8% 48 vs. 6.5% 49 ) were seen when the same test brand (FOB Gold) was applied at an identical threshold (10 mg Hb/ g feces). In our study, we could show that the adjustment of the threshold value to yield a certain PR would have led to almost identical specificities and a much narrower range of sensitivities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, two population-based studies conducted in Latvia and in the Netherlands observed significant differences in PRs between two different FIT brands (OC Sensor and FOB Gold), in spite of applying an identical threshold (10 mg Hb/g feces). 48,49 Furthermore, even large differences in the PR (12.8% 48 vs. 6.5% 49 ) were seen when the same test brand (FOB Gold) was applied at an identical threshold (10 mg Hb/ g feces). In our study, we could show that the adjustment of the threshold value to yield a certain PR would have led to almost identical specificities and a much narrower range of sensitivities.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Furthermore, even large differences in the PR (12.8% 48 vs. 6.5% 49 ) were seen when the same test brand (FOB Gold) was applied at an identical threshold (10 mg Hb/ g feces). 48,49 Furthermore, even large differences in the PR (12.8% 48 vs. 6.5% 49 ) were seen when the same test brand (FOB Gold) was applied at an identical threshold (10 mg Hb/ g feces).…”
Section: Discussionmentioning
confidence: 99%
“…However, setting a higher f-Hb cut-off criterion for the PR with the OC-Sensor at subsequent rounds, to achieve the same PR with the two systems (29 µg Hb/g faeces rather than 20 µg Hb/g faeces) would result in a similar diagnostic performance. Grobbee et al 12 have pointed out recently that comparison between FIT systems is usually done at the same f-Hb. Our findings support their thesis that improved comparison on diagnostic yield would be achieved with PR rather than f-Hb.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the observed difference in the PR between the two systems at subsequent but not at first round, when using the same standardised f-Hb cut-off need to be investigated. The lower prevalence of neoplasia among people with previous negative results might result in lower average f-Hb and, for a number of reasons,12 different methods might show different performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation